G521(P) Baby friendly prevention and management of neonatal hypoglycaemia on postnatal wards. (27th April 2015) - Matthews, C; Sage, E; Reynolds, P
Abstract : Context: The project was undertaken at a level 3 NICU in a DGH in Surrey, UK, involving junior and senior doctors, midwives, nursery nurses, pharmacists and the pathology department. Problem: Staff anecdotally felt the hypoglycaemia operational threshold was too high, monitors were inaccurate, blood sugar level (BSL) tests too frequent and management inconsistent. Treatment with formula feed supplements was hindering efforts to establish breastfeeding and prolonging stays. Assessment of problem and analysis of its causes: Initial assessment involved an audit of current practice against Baby-Friendly Initiative standards and interviews with 62 multidisciplinary team members to explore concerns and collate ideas for improvement. To check equipment accuracy, 50 samples were tested for blood glucose on both the portable metres and blood gas machine, which found on average glucosmeters under-read by 0.5mmol/L (range 0–2.0mmol/L). A review of literature and other UK trust's policies was carried out to identify best practice and alternatives to formula-feed supplementation. It was recognised that new equipment would need to be used for BSL monitoring and all staff would need to be trained in any policy changes. Intervention: New guidelines lowered the working definition of hypoglycaemia, limited the number of BSL tests performed by stopping routine measurement of post-feed BSLs, and changed first line treatment of moderate hypoglycaemia (BSL >2mmol/L) from formula top-up to dextrose gel. A new proforma with step-by-step management plan and built in escalation was designed with the midwives. The pathology department is acquiring more accurate glucosmeters for the trust; in the meantime a "glucose only" micro-sample setting on NICU gas machine has been set up. Study design: Audit of practice pre- and post- new management guidelines was undertaken to measure the number of needle pricks each baby had, number of days each infant at risk of hypoglycaemia was monitored for, supplementation rates, the number of babies treated for hypoglycaemia who were discharged breast feeding and still doing so at 3 months, and the number of infants admitted to NICU for management of hypoglycaemia. Strategy for change: Management of hypoglycaemia guidelines were re-written and a new proforma produced within 6 months. This was sent to all Neonatal Consultants and senior midwives for review. All midwives and nursery nurses were trained by the authors and the point-of-care team in the new guidelines, how to take a capillary blood gas and how to run a glucose only sample. Audit of practice as outlined above was carried out for infants treated 6 months before and 6 months after guideline implementation, and the results fed back to the Neonatal Consultant body. Measurement of improvement: Audit of practice showed post-implementation the average number of BSL tests per baby reduced by 73% (15 to 4 pricks) and average monitoring time reduced by 52%- saving 520hrs/month staff time. Breastfeeding rates at 3 months post discharge have doubled and provisional data shows a 38% reduction in SCU/NICU admissions for neonatal hypoglycaemia. Effects of changes: Changes implemented meant more accurate blood sugar analysis, fewer needle pricks for infants, shorter admission time for infants at risk of hypoglycaemia, and decreased use of formula supplementation which has enabled the trust to apply for Level 3 Baby Friendly accreditation. Some senior staff were concerned the new proforma was too complicated; this was addressed through face-to-face consultation. Lessons learnt: The most important lesson was the necessity of having all members of the multi-disciplinary team involved in the project from the beginning. Message for others: Change to the status quo to improve patient care and experience is possible by quantifying a long-standing anecdotal problem and implementing evidence based practice.